European foreign and security policy challenges and opportunities for the German EU presidency - Volker Perthes; Stefan Mair (Stiftung Wissenschaft und Politik (SWP), 2006)
Expectations placed on the German EU presidency in the first half of 2007 are especially high: Besides the current work that needs to be processed efficiently and cooperatively, each EU presidency has the opportunity to put items on the agenda that it considers to be especially important. Today, for the EU member states, foreign and security policy is ultimately only conceivable in a European framework. This is made very clear in the European Security Strategy of 2003, the fundamental policy statement for European foreign and security policy. None of the risks described there could be dealt with on a national level. For all their scepticism about the EU, the populations of the EU member states have certainly recognized this and wish for "more Europe" especially in foreign and security policies. More coherence, more joint European foreign and security activity, and greater visibility of the EU as an international player can consequentially also serve to strengthen public confidence in the European project in individual European countries.This collection of 16 contributions by researchers at Stiftung Wissenschaft und Politik, the German Institute for International and Security Affairs, deals with the foreign and security issues that we believe will gain particular relevance for the EU during the German presidency. Rather than addressing all aspects of European foreign and security policy, we concentrate on a small selection where a heightened need for action is to be expected, and also look at others that call for initiatives whose timeframe extends beyond the first half of 2007
Keywords: 320